Globalized mathematics curriculum: could it ever be possible? (2019)
It is a known fact that the world now is a global village. Almost every aspect of human endeavor is moving with space in this era of digitization and movement with ethos of ages. The teaching of mathematics has been polarized in term of introduction of cultural diversity from other countries. Within standardized curricula, concepts and teaching are largely dissociated from the knowledge and skills a child brings into the classroom. Unless learners realize that mathematics exist in their very own world, beyond school walls and beyond a Eurocentric worldview, many of them will continue to complain about it as boring and uninteresting. Universalizing the curriculum for the sake of simplifying assessment or selling textbooks is not going to minimize the anxiety or even hatred that many students feel towards numbers. Conversely, introducing everyday mathematics into curricula will help students understand that math is something related to their culture.